Intervariant Linguistic Phenomena in Semantic “Baking” in National Variants of Spanish - N. F. Mikheeva; E. A. Popova; Z. N. Ignashina (Научный диалог)
The article deals with the issue of semantic discrepancies between the lexical units of the Spanish language national variants on the example of the semantic field “Bread and baking” lexemes. The relevance of the study is due to its focus on the needs of the current stage of development of comparative semantics, variantology and intervariant dialectology, which provide for the gradual coverage of all the supporting semantic fields of the language in the communicative-pragmatic aspect. The novelty of the study is seen in the fact that through a comparative intervariant analysis of language units with the primary meaning of baking, the cultural specificity of the corresponding concepts in different Spanish-speaking countries and regions within the framework of a multinational language is revealed. Particular attention is paid to the semantic processes and linguistic phenomena underlying the intervariant discrepancies, their classification is proposed in relation to this area. The question is raised about the importance of extralinguistic factors in the formation of the alimentary thesaurus of a particular country and culture or sets of cultures in a certain territory. As a result of the study, it was proved that the vocabulary of the field “Baking” is a source of difficulties in intercultural communication, directly related to linguistic phenomena in the field of variantology and intervariant dialectology of the Spanish language.